AHP-based evaluation of critical barriers for social distancing in India during COVID-19 pandemic. (28th December 2021) - Upadhyay, Hemant; Juneja, Abhinav; Juneja, Sapna; Gupta, Deepak
COVID-19 has made the world realise, the uncertainty of our existence on the planet. There have been unprecedented consequences of the spread of this deadly pandemic. New methods and theories are being proposed by research community to save the humans from being affected by this disease. The aim of the presented research work is to analyse the critical barriers in social distancing in India during COVID-19 using AHP technique. Expert opinions are utilised to identify critical barriers in self-distancing in India during COVID-19. Twelve critical barriers have been identified, compared and evaluated using analytic hierarchical process (AHP) method to get ranked in terms of priorities for preventing the spread of pandemic. The results may be utilised by the policy creators for nurturing adequate reforms and policies to effectively deal with current pandemic considering the relative importance of these critical barriers in social distancing management.